USE OF INFORMATION TECHNOLOGY INTERNET-BASED SYSTEM «MOODLE» TO TEACHING THE DISCIPLINE “HISTOLOGY, CYTOLOGY AND EMBRYOLOGY” - Boychuk, T.M.; Khodorovska, A.A.; Malyk, Yu.Yu.; Petryshen, O.I. (World of Medicine and Biology, 2012)
This work shows the questions of use of informative-communication study technologies on the basis of management system of study “MOODLE” at teaching the discipline “Histology, cytology and embryology”.
Keywords: of Informatively-communication technologies; "MOODLE"